(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La nozione di ministro di culto nell’ordinamento italiano - 2. Origini storiche della figura civilistica del ministro di culto - 3. Principi ispiratori dell’attuale normativa sui ministri di culto - 4. La normativa sui ministri di culto: le fonti - 5. Disposizioni restrittive sui ministri di culto - 6. I ministri di culto nel diritto penale - 7. I ministri di culto nella legislazione pattizia - 8. Ministri di culto e giurisdizione confessionale, tra autonomia e tutela dei diritti - 9. Il sostentamento dei ministri di culto - 10. La remunerazione del ministro di culto: natura della prestazione e tutela giurisdizionale - 11. Le molteplici attività socialmente rilevanti dei ministri di culto - 12. Problemi, vecchi e nuovi, e prospettive di riforma - 13. Osservazioni conclusive. The ministers of religion in Italian law ABSTRACT: This contribution analyses the status of ministers of religion in the Italian legal system. It starts from a description of the historical foundations, which lies in Nineteenth-century liberal legislation, and arrives at a synthetic representation of the regulations currently in force in the unilateral State law and in the Concordat and Treaty legislation. The regulatory evolution, which is still in progress, describes the transition from a uniform and homogeneous concept of minister of religion, inspired by the Catholic priest and placed at the basis of a mostly restrictive legislation, to a more articulate and comprehensive one, reflecting the growing confessional pluralism of Italian society and the assertion of the right to religious freedom. This new approach represents the premise for a legislation that increasingly aims at protecting and promoting the status and the manifold activities of ministers of religion, particularly in the context of the strong enhancement of the Welfare State and of the Third sector. Finally, the article focuses on some problematic issues of the current legislation and on the apparent paradox that, in the face of a more favorable State legislation, nowadays the status of the minister of religion, and in particular that of the Catholic priest - who still represents the main reference for Italy’s legislation - is undergoing a strong identity crisis in the ecclesial order, thus posing a series of problems also for society at large.